A Profile of West European Neutralism. - United States. International Communication Agency. Office of Research.; Winn, Gregory F.T. (Tufts University. Tisch Library., 2019)
At present, we do not have an assessment of the possible impact of the current anti-nuclear demonstrations on West European public opinion. However, surveys as recent as July show that prevailing West European views are-usually more upbeat with respect to the U.S. and its security policies than is generally reflected in domestic and foreign media. Nonetheless, if minority sentiments, such as "neutralism ," become -- or are perceived to be -- prevailing views, serious difficulties between the U.S. and its NATO allies would lie ahead. In view of the concern that neutralism may be "sweeping" Europe, this paper tries to throw light on some of the attitudes that coalesce around support for neutrality in several West European countries.; Research Memorandum M-10/28/81